Effects of family cohesion and heart rate reactivity on aggressive/rule-breaking behavior and prosocial behavior in adolescence: The Tracking Adolescents' Individual Lives Survey study. (23rd July 2013) - Sijtsema, Jelle Jurrit; Nederhof, Esther; Veenstra, Rene; Ormel, Johan; Oldehinkel, Albertine J.; Ellis, Bruce J.
Abstract: The biological sensitivity to context hypothesis posits that high physiological reactivity (i.e., increases in arousal from baseline) constitutes heightened sensitivity to environmental influences, for better or worse. To test this hypothesis, we examined the interactive effects of family cohesion and heart rate reactivity to a public speaking task on aggressive/rule-breaking and prosocial behavior in a large sample of adolescents ( N = 679; M age = 16.14). Multivariate analyses revealed small- to medium-sized main effects of lower family cohesion and lower heart rate reactivity on higher levels of aggressive/rule-breaking and lower levels of prosocial behavior. Although there was some evidence of three-way interactions among family cohesion, heart rate reactivity, and sex in predicting these outcome variables, these interactions were not in the direction predicted by the biological sensitivity to context hypothesis. Instead, heightened reactivity appeared to operate as a protective factor against family adversity, rather than as a susceptibility factor. The results of the present study raise the possibility that stress reactivity may no longer operate as a mechanism of differential susceptibility in adolescence.